Numerical Simulation and Experimental Study on Internal Depressurization Flow Characteristics of a Multi-layer Sleeve Regulating Valve - H. Z. Jin; K. M. Tang; X. F. Liu; C. Wang (Journal of Applied Fluid Mechanics, 2023)
The sleeve regulating valve is an important part of a pipeline system and is widely used in the fields of nuclear power and thermal power. In this study, a series of numerical and experimental studies are performed to understand the depressurized flow characteristics inside a new type of multi-layer sleeve regulating valve. In the calculations, the standard k-ԑ turbulence model and the mixture model combined with the Zwart–Gerber–Belamri cavitation model are used to clarify the internal flow and cavitation characteristics in the regulating valve. With the new valve, the results show that when the valve is fully opened, the pressure drop at all levels of the valve is comparatively average (approximately 2–3 MPa for each level) and the fluid velocity in the sleeves at all levels is comparatively uniform at 90 m/s—which can prevent the valve from being eroded by highly changing fluid flow rates, and also offers ideal pressure reduction performance. To reduce the degree of cavitation, it is recommended to adjust the outlet pressure of the valve to 0.7 MPa.